Player recruitment strategies in English Premier League football 1990-2008: Progession of home-grown players - Littlewood, M.; Elliot, C.; Richardson, D. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Throughout history, football labour migration has been a common feature of the industry, however the speed and volume of such labour migration has been the centre of much debate (Maguire & Pearton, 2000; UEFA, 2005). Concerns focus on the de-skilling of donor nations and the dependant development of host countries by acquiring talent from donor nations (Darby, 2005). The introduction of the 4+4 rule by UEFA (UEFA, 2005) and FIFA`s proposed 6+5 rule by 2012 are both attempts to safeguard the development and progression of homegrown players. The study examined the player recruitment strategies of English Premier League professional football clubs over 18 seasons. More specifically, it aimed to determine the presence and impact of home-grown players. Method: Data was collated via a number of official player directories (i.e., Rothmans Football Yearbooks, 1990-2004 & Sky Sports Football Yearbooks 2004-2008) for all registered professional football players from seven English Premier League (EPL) clubs that had remained in the league consistently from 1990/91 to 2008/09. Data was systematically inputted into the Statistical Package for Social Scientists (SPSS V17). The coding of specific variables in the database enabled the effective management and analysis (descriptive statistics) of a vast amount of quantitative data (2959 entries). Results: Findings revealed that over the time period, professional football players (excluding homegrown players) were predominantly acquired from countries within the UEFA confederation of FIFA (N=645, 85%). Analysis also suggested players from both Africa and South America (N=49, 6.5% & N=37, 4.9%) were favoured non-UEFA confederations by the sample of clubs. The presence of home-grown players throughout the time period increased, with indigenous English home-grown players occupying the largest acquisition frequency (N=561, 76%). When analysing player type appearances, Figure 1 indicates that the percentage contribution of home-grown players remained relatively stable over time with a decrease from 2004/05 onwards. The decreasing trend was also evident in English and UK and Rep Ireland players, whilst European and non-European players evidenced significant increases in appearances over time (40% and 18% of total player appearances in 2008/09 respectively). Conclusion: Football labour migration was prevalent and suggested that clubs adopted global recruitment strategies, drawing players from all of the respective FIFA confederations. The dominant players originated from countries in UEFA, South America and Africa. This accentuates the EPL clubs` power in terms of de-skilling of peripheral nation states and may result in the EPL becoming a dependent development league. This will be more extreme for those clubs that fail to invest in youth development. Whilst the presence of home-grown players was apparent, their relative impact in terms of appearances over time decreased and further highlights the lack of meaningful competitive football for those young players progressing through elite development programmes in the EPL.